Maritime Transport And Port Services In Algeria - Annane, Rachid; Hachemane ,Mouloud (جامعة الوادي University of Eloued, 2024)
The maritime transport sector in Algeria is evolving with investments aimed at modernizing fleets and port infrastructure. Despite this, only 3% of the national fleet is dedicated to imports. In 2021, trade in transport services reached $9.7 billion, mainly thanks to international trade which totaled $72.7 billion. Algerian ports welcome nearly 10,000 ships per year, transporting more than 20 million tons of goods, excluding hydrocarbons. However, they only capture 10% of Mediterranean traffic, thus limiting the potential for economic development. The maximum contribution of port services to GDP is 0.2%. Despite modernization efforts, challenges persist, particularly in terms of inadequate infrastructure and insufficient logistics coordination. Nevertheless, this sector offers development opportunities within the framework of the blue economy. To strengthen the contribution to national growth, additional investments in modernization and training of personnel, as well as better coordination between actors, are necessary.
Keywords: Maritime transport; Ports; Development; Services; Logistics